Understanding FinTech Adoption in Equity Trading Platforms: An Extended UTAUT2 and Trust-Based Approach - K, Shriya; T, Velmurugan (Asian Journal of Interdisciplinary Research, 2025)
This study examines the determinants of FinTech adoption among millennial investors with focus on emerging equity markets. The study mainly focuses on trust and perceived transparency within an extended Unified Theory of Acceptance and Use of Technology (UTAUT2) framework. The work utilises real-time data collected from 352 respondents, which is analysed through SPSS and AMOS. The model explains 62.4% of the variance in behavioural intention and 33.7% in actual FinTech use. Performance expectancy (β = 0.216, p < 0.01), social influence (β = 0.134, p < 0.01), perceived transparency (β = 0.161, p < 0.01) and facilitating conditions (β = 0.109, p < 0.05) significantly enhance intention, while perceived risk (β = 0.098, p < 0.05) reduces it. The study identified that Behavioural intention acts as a mediator linking UTAUT2 constructs to actual investment behaviour. In addition, the work also underscores that trust moderates the strength of this relationship, amplifying the translation of intention into action. This study offers a strategic guidance for FinTech developers to broaden the utilisation of the digital tools in emerging equity markets.